"I have a dream" a 50th year testament to the march that changed America - Adelman, Bob (Pearson Education, 2013)
Presents a narrative and pictorial history of the 1963 March on Washington, depicting ordinary marchers along with some of the major figures of the twentieth-century Civil Rights Movement.
Online resource; title from title page (Safari, viewed September 17, 2013)
Keywords: March on Washington for Jobs and Freedom -- Washington, D.C.) -- (1963 -- Pictorial works; Civil rights demonstrations -- Pictorial works -- History -- 20th century -- Washington (D.C.); African Americans -- Pictorial works -- Civil rights -- History -- 20th century; March on Washington for Jobs and Freedom / (1963 / Washington, D.C.) / Pictorial works; March on Washington for Jobs and Freedom; 1900-1999; Noirs américains; Droits; Histoire; 20e siècle; Ouvrages illustrés; African Americans; Civil rights; Civil rights demonstrations; Washington (D.C.); History; Pictorial works